ответ:
пусть через х лет возраст отца будет в 2 раза больше суммы возрастов детей. уравнение:
34 + х = (3 + х + 5 + х) * 2
34 + х = (8 + 2х) * 2
34 + х = 16 + 4х
34 - 16 = 4х - х
3х = 18
х = 18 : 3
х = 6
ответ: через 6 лет.
проверка: 34 + 6 = (3 + 6 + 5 + 6) * 2
40 = 20 * 2
40 = 40
пошаговое объяснение:
ответ:
пусть через х лет возраст отца будет в 2 раза больше суммы возрастов детей. уравнение:
34 + х = (3 + х + 5 + х) * 2
34 + х = (8 + 2х) * 2
34 + х = 16 + 4х
34 - 16 = 4х - х
3х = 18
х = 18 : 3
х = 6
ответ: через 6 лет.
проверка: 34 + 6 = (3 + 6 + 5 + 6) * 2
40 = 20 * 2
40 = 40
пошаговое объяснение: